Self‐refraction, ready‐made glasses and quality of life among rural myopic Chinese children: a non‐inferiority randomized trial. Issue 6 (20th June 2016) - Zhou, Zhongqiang; Chen, Tingting; Jin, Ling; Zheng, Dongxing; Chen, Shangji; He, Mingguang; Silver, Josh; Ellwein, Leon; Moore, Bruce; Congdon, Nathan G.
Abstract: Purpose: To study, for the first time, the effect of wearing ready‐made glasses and glasses with power determined by self‐refraction on children's quality of life. Methods: This is a randomized, double‐masked non‐inferiority trial. Children in grades 7 and 8 (age 12–15 years) in nine Chinese secondary schools, with presenting visual acuity (VA) ≤6/12 improved with refraction to ≥6/7.5 bilaterally, refractive error ≤−1.0 D and <2.0 D of anisometropia and astigmatism bilaterally, were randomized to receive ready‐made spectacles (RM) or identical‐appearing spectacles with power determined by: subjective cycloplegic retinoscopy by a university optometrist (U), a rural refractionist (R) or non‐cycloplegic self‐refraction (SR). Main study outcome was global score on the National Eye Institute Refractive Error Quality of Life‐42 (NEI‐RQL‐42) after 2 months of wearing study glasses, comparing other groups with the U group, adjusting for baseline score. Results: Only one child (0.18%) was excluded for anisometropia or astigmatism. A total of 426 eligible subjects (mean age 14.2 years, 84.5% without glasses at baseline) were allocated to U [103 (24.2%)], RM [113 (26.5%)], R [108 (25.4%)] and SR [102 (23.9%)] groups, respectively. Baseline and endline score data were available for 398 (93.4%) of subjects. In multiple regression models adjusting for baseline score, older age (p = 0.003) and baseline spectacle wear (p = 0.016), but not study group assignment, were significantly associated with lower final score. Conclusion: Quality of life wearing ready‐mades or glasses based on self‐refraction did not differ from that with cycloplegic refraction by an experienced optometrist in this non‐inferiority trial